Changes of land cover in the Al-Sanamayn area in Daraa Governorate between 2000-2020 using remote sensing (Damascus University Journal of arts and humanities sciences, 2025)
The research aims to reveal the changes that occurred in (vegetation cover - urban areas - barren lands) in the Al-Sanamayn region between 2000 and 2020 AD, and to identify these changes and how they changed during the studied period, and to prepare maps showing the results of applying the supervised and unsupervised classification in the region during the period The time studied using remote sensing techniques and geographic information systems, because of their great role in saving effort, material cost and shortening time, in addition to the possibility of obtaining results with high accuracy and reliability. The changes in the land cover (vegetation cover - urban areas - barren lands) that affected the region were determined by classifying satellite images that helped obtain information about the land cover in the research area, and it was found that there are clear differences in the region in vegetation cover, urban areas and lands. Barren between thetwo studied years.How the vegetation cover changed during the studied time period was evaluated using the NDVI vegetation index, and it was found that the plant density is high in 2020 and increased in the western part of the region and the southern part compared to these parts in the year 2000 AD, and the agricultural exploitation of the land due to the increase in the population’s need for food. Accordingly, maps were prepared and designed to show the results of applying the supervised and unsupervised classification in the region during the studied time period. It was found that the residential agglomerations increased from 28% to 63% at the expense of agricultural lands and barren lands, after the end of the Syrian war and the return of the population to their lands, and the decrease in the area of agricultural lands from 34% to 22%, and barren lands from 38% to 15%. The population leads to an increase in their food needs and thus an increase in their food requirements, and this had a negative impact on agricultural lands.
Keywords: :Remote sensing (RS); Geographic information systems (GIS); satellite images; NDVI; controlled taxonomy; unattended taxonomy; Al-Sanamayn area